Stock market returns and macroeconomic variables in nigeria: testing for dynamic linkages with a structural break - Ali, Umar Ahmad; Abdullah, Adam; Ahmad, Tijjani Abdullahi; Umar, Abdul Aziz Muhammad (SAS Publishers, 2015)
The paper analysed the dynamic interactions between two macroeconomic variables and stock market returns in Nigeria from 1970-2013, using F-Bound Cointegration and Todayamamoto Causality tests that are robust to structural breaks. The result of Zivot Andrew unit root test indicated that all the variables were non stationary at level but stationary at first difference. The result of ARDL F-Bound Test to cointegration also indicated that cointegration exist among the variables. In the sense of Causality Test, there is a strong evidence of uni-directional causality from per capita income to stock market returns and from inflation to stock market returns.It is also indicated that gross domestic per capita income and inflation jointly caused the stock market returns. In the context of policy implications, this study suggests that government should formulate appropriate policy to encourage investment in financial markets which in resulting stimulate economic growth.